2009
DOI: 10.1186/cc7153
|View full text |Cite
|
Sign up to set email alerts
|

Bench-to-bedside review: Angiopoietin signalling in critical illness – a future target?

Abstract: Multiple organ dysfunction syndrome (MODS) occurs in response to major insults such as sepsis, severe haemorrhage, trauma, major surgery and pancreatitis. The mortality rate is high despite intensive supportive care. The pathophysiological mechanism underlying MODS are not entirely clear, although several have been proposed. Overwhelming inflammation, immunoparesis, occult oxygen debt and other mechanisms have been investigated, and -despite many unanswered questions -therapies targeting these mechanisms have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
112
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 182 publications
(228 reference statements)
1
112
0
12
Order By: Relevance
“…To the best of our knowledge, this is one of the initial reports to demonstrate regulation of Ang2 expression and proinflammatory angiogenesis by Nox-dependent signaling. Increased Ang2 expression in the systemic circulation or in the lung has been associated with mortality in humans with sepsis, severity of acute lung injury, and with development of BPD in premature infants (30,31,51). Although we showed that mouse lung endothelial cells express increased Ang2 and Tie2 after systemic LPS, the rest of our data were obtained in primary cells in vitro, and, therefore, verification of the results of this study in animal models expressing angiogenic factors in a tissue-restricted manner will enable us to better understand the significance of these findings.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is one of the initial reports to demonstrate regulation of Ang2 expression and proinflammatory angiogenesis by Nox-dependent signaling. Increased Ang2 expression in the systemic circulation or in the lung has been associated with mortality in humans with sepsis, severity of acute lung injury, and with development of BPD in premature infants (30,31,51). Although we showed that mouse lung endothelial cells express increased Ang2 and Tie2 after systemic LPS, the rest of our data were obtained in primary cells in vitro, and, therefore, verification of the results of this study in animal models expressing angiogenic factors in a tissue-restricted manner will enable us to better understand the significance of these findings.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Although we showed that mouse lung endothelial cells express increased Ang2 and Tie2 after systemic LPS, the rest of our data were obtained in primary cells in vitro, and, therefore, verification of the results of this study in animal models expressing angiogenic factors in a tissue-restricted manner will enable us to better understand the significance of these findings. This assumes translational significance because inhibiting Ang2 using antibodies or modulating Nox2 activity are emerging as promising strategies to decrease lung injury in bacterial sepsis (51,52).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…9 Angiopoietin-1-mediated Tie2 activation maintains the quiescent state of the endothelium by stabilizing endothelial cell-cell junctions and by countering the permeabilizing effects of VEGF. 10 Angiopoietin-2 antagonizes the effects of Ang-1; it destabilizes the endothelium by disrupting cell-cell adhesion and primes the endothelial cells to the effects of pro-inflammatory cytokines and VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…As circulating or matrix-bound molecules, angiopoietin-1 (Ang-1) and its antagonist angiopoietin-2 (Ang-2) bind to the extracellular domain of the receptor tyrosine kinase Tie2, which is almost exclusively expressed on endothelial cells [15][16][17]. Produced by vascular smooth muscle cells (SMCs) and precursor pericytes, Ang-1-induced activation of the Tie2 receptor promotes quiescence and structural integrity of mature vessels, thus protecting the endothelium from activation by cytokines and growth factors [18][19][20][21][22][23]. In contrast, Ang-2 disrupts the constitutive Ang-1/Tie2 signaling by preventing Ang-1 from binding to the common receptor [15,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%